The Impact of Transparent Dressings on Phlebitis Incidence in Pediatric Intra Venous Therapy - Dwijayanti, Ni Kadek Rai; Resiyanthi, Ni Komang Ayu; Yanti, Ni Luh Gede Puspita; Arwidiana , Dewa Putu (Basic and Applied Nursing Research Journal, 2024)
Introduction: Hospitalization can be a traumatic experience for both children and their parents. During the hospitalization process, procedures such as installing an IV drip can lead to phlebitis infection. To prevent phlebitis, nurses often use transparent dressings when installing a child's IV. The aim of this study was to determine the relationship between the use of transparent dressings and the incidence of phlebitis during pediatric IV drips. Methods: This study employed a descriptive correlational research design with a cross-sectional approach. The total sample consisted of 40 individuals selected through accidental sampling. Data collection tools included questionnaires and observation sheets. Results: Among the 40 respondents, transparent dressings were used 100% of the time, and the incidence of phlebitis was observed in 2 respondents (5%). The results of the Spearman Rank analysis test showed a p-value of 0.288, indicating no significant relationship between the use of transparent dressings and the incidence of phlebitis in children's IV installations. The Spearman correlation coefficient between the use of transparent dressings and the incidence of phlebitis was 0.172, suggesting a very weak correlation. Discussion: Many factors can contribute to the development of phlebitis. While the use of transparent dressings can help nurses observe and detect signs of phlebitis more easily, this study found no significant correlation between their use and the incidence of phlebitis. However, transparent dressings can still be beneficial for early detection and intervention.